Haemodynamic evidence for cardiac stress during transurethral prostatectomy. Issue 6828 (14th March 1992) - Evans, J. W.; Singer, M.; Chapple, C. R.; Macartney, N.; Walker, J. M.; Milroy, E. J.
Abstract : OBJECTIVE--To compare haemodynamic performance during transurethral prostatectomy and non-endoscopic control procedures similar in duration and surgical trauma. DESIGN--Controlled comparative study. SETTING--London teaching hospital. PATIENTS--33 men aged 50-85 years in American Society of Anesthesiologists risk groups I and II undergoing transurethral prostatectomy (20), herniorrhaphy (eight), or testicular exploration (five). MAIN OUTCOME MEASURES--Percentage change from baseline in mean arterial pressure, heart rate, Doppler indices of stroke volume and cardiac output, and index of systemic vascular resistance, and change from baseline in core temperature. RESULTS--In the control group mean arterial pressure fell to 11% (95% confidence interval -17% to -5%) below baseline at two minutes into surgery and remained below baseline; there were no other overall changes in haemodynamic variables and the core temperature was stable. During transurethral prostatectomy mean arterial pressure increased by 16% (5% to 27%) at the two minute recording and remained raised throughout. Bradycardia reached -7% (-14% to 1%) by the end of the procedure. Doppler indices of stroke volume fell progressively to 15% (-24% to -6%) below baseline at the end of the procedure, and the index of cardiac output fell to 21% (-32% to -10%) below baseline by the end of the procedure. The index of systemic vascular resistance was increased by 28% (17% to 38%) at two minutes, and by 46.8% (28% to 66%) at the end of the procedure. Core temperature fell by a mean of 0.8 (-1.0 to -0.6) degrees C. Significant differences existed between the two groups in summary measures of mean arterial pressure (p less than 0.05), Doppler indices of stroke volume (p less than 0.005) and cardiac output (p less than 0.005), index of systemic vascular resistance (p less than 0.0005), and core temperature (p less than 0.0001). CONCLUSIONS--Important haemodynamic disturbances were identified during routine apparently uneventful transurethral prostatectomy but not during control procedures. These responses may be related to the rapid central cooling observed during transurethral prostatectomy and require further study.